The effect of workload on employee burnout: A study of civil servants in East Kalimantan: - - Nur Khairunnisa; Dian Dwi Nur Rahmah (Jurnal Psikologi Tabularasa, 2025)
High workloads in government agencies, if not managed properly, can lead to boredom as well as physical and mental fatigue, which in turn may trigger burnout. This study aims to examine the effect of workload on burnout. The research employed a quantitative approach with 50 employees of UPTD X in East Kalimantan Province as subjects, selected through a total sampling technique. Data were analyzed using simple linear regression. The results showed a significant effect of workload on burnout with a p-value = 0.000 (p < 0.05). The contribution of workload to burnout was 69.7%. Based on these findings, UPTD X in East Kalimantan Province is advised to implement a transparent performance management system aligned with the main tasks and roles of each employee and to ensure a fair distribution of assignments across all employees.